The European social fund supports the reintegration of the long-term unemployed individuals aged 50+ into the labor market: A comparison of the Federal States in Austria - Azra Kadri; Vito Bobek; Tatjana Horvat (Naše gospodarstvo / Our Economy, 2021)
This paper shows the importance of European Social Fund's (ESF) countermeasures for reintegrating long-term unemployed persons aged 50+ in Austria since their number has increased in recent years. Four research questions are defined, which deal with the theoretical background, the ESF's contribution, the possible causes of long-term unemployment, and their reflection in a country comparison figures. For the qualitative methodology, we conducted expert interviews and case study analysis. Concerning the quantitative method, we evaluated raw data from the AMS Public Employment Service, Austria, and Statistics, Austria. A correlation was established based on the content-related evaluation of the theoretical approaches, the expert analysis, and the presentation of statistics. It is necessary to identify the causes in time and take appropriate measures to prevent them from combating longterm unemployment among this target group.
Keywords: M64; 330; labor market; long-term unemployed aged 50+; the European Social Fund; Austria